2018
DOI: 10.1007/s00429-018-1747-5
|View full text |Cite
|
Sign up to set email alerts
|

General intelligence is associated with working memory-related brain activity: new evidence from a large sample study

Abstract: Psychometric intelligence is closely related to working memory capacity. Here we aim to determine the associations of neural activation patterns during the N-back working memory paradigm with psychometric intelligence and working memory performance. We solved the statistical problems of previous studies using (1) a large cohort of 1235 young adults and (2) robust voxel-by-voxel permutation-based statistics at the whole-brain level. Many of the significant correlations were weak, and our findings were not consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 51 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Working memory is a limited capacity storage system that is used to hold and manipulate information over short periods of time [164,165]. Working memory capacity can be increased through training, and correlates closely with measures of "general intelligence" in humans [166]. We trained mice in a T-maze "rewarded alternation" task that relies mainly on short-term memory function, arguably analogous to human working memory.…”
Section: Working Memory Trainingmentioning
confidence: 99%
“…Working memory is a limited capacity storage system that is used to hold and manipulate information over short periods of time [164,165]. Working memory capacity can be increased through training, and correlates closely with measures of "general intelligence" in humans [166]. We trained mice in a T-maze "rewarded alternation" task that relies mainly on short-term memory function, arguably analogous to human working memory.…”
Section: Working Memory Trainingmentioning
confidence: 99%
“…This demonstrates an inability of Myrf- cKO mice to improve their spatial working memory performance. The requirement for OL genesis in working memory training is intriguing because working memory capacity is known to underpin all kinds of cognitive abilities and correlates closely with measures of intelligence in humans and animals (Conway et al, 2003; Matzel and Kolata, 2010; Johnson et al, 2013; Takeuchi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that working memory brain activity is closely related to fluid intelligence but does not fully explain its variability (Takeuchi et al. , 2018). Thus, including interaction effects between brain activities under different memory load conditions offers a great potential to enhance the prediction on general cognitive ability.…”
Section: Methodsmentioning
confidence: 99%
“…In the ABCD application with the goal to investigate how functional brain activation under different memory conditions associates with general cognitive abil-ity , we consider three functional brain activation contrast maps derived from the emotional 𝑛-back fMRI data using Statistical parametric mapping (SPM) software (Penny et al, 2011) to measure the low memory load brain activity (0-back vs. baseline), high memory load brain activity (2-back vs. baseline) and working memory brain activity (2-back vs. 0-back). It has been shown that working memory brain activity is closely related to fluid intelligence but does not fully explain its variability (Takeuchi et al, 2018). Thus, including interaction effects between brain activities under different memory load conditions offers a great potential to enhance the prediction on general cognitive ability.…”
Section: Methodsmentioning
confidence: 99%